Conversations on faith - Scorsese, Martin; Spadaro, Antonio (Grand Central Publishing, 2025)
"From his Italian-American upbringing as a Catholic in New York to the meditations on religion, belief, and the divine found in his filmography, Martin Scorsese's relationship to his faith has touched every aspect of his life and work. When Italian journalist Father Antonio Spadaro and Martin Scorsese first sat down together in Scorsese's home, neither could have predicted the depth of the conversation, intellectual exchange, or friendship that would result. While discussing the acclaimed director's film Silence, about the persecution of Jesuits in Japan, they began a dialogue about faith that continues to this day. In their often-profound conversations, he and Father Spadaro have left no stone unturned, discussing this relationship along with everything from Scorsese's childhood to the concept of the soul. And as a result of their long friendship and communication, Scorsese met with Pope Francis. Readers will gain new insight into one of the most famous directors of the twentieth and twenty-first centuries in these honest, moving, and ultimately inspiring Conversations on Faith." --